Adaptation of Cryo‐Sectioning for IEM Labeling of Asymmetric Samples: A Study Using Caenorhabditis elegans. (6th May 2015) - Nicolle, Ophélie; Burel, Agnès; Griffiths, Gareth; Michaux, Grégoire; Kolotuev, Irina
<x xml:space="preserve">Abstract</x> Cryo‐sectioning procedures, initially developed by Tokuyasu, have been successfully improved for tissues and cultured cells, enabling efficient protein localization on the ultrastructural level. Without a standard procedure applicable to any sample, currently existing protocols must be individually modified for each model organism or asymmetric sample. Here, we describe our method that enables reproducible cryo‐sectioning of Caenorhabditis elegans larvae/adults and embryos. We have established a chemical‐fixation procedure in which flat embedding considerably simplifies manipulation and lateral orientation of larvae or adults. To bypass the limitations of chemical fixation, we have improved the hybrid cryo‐immobilization–rehydration technique and reduced the overall time required to complete this procedure. Using our procedures, precise cryo‐sectioning orientation can be combined with good ultrastructural preservation and efficient immuno‐electron microscopy protein localization. Also, GFP fluorescence can be efficiently preserved, permitting a direct correlation of the fluorescent signal and its subcellular localization. Although developed for C. elegans samples, our method addresses the challenge of working with small asymmetric samples in general, and thus could be used to improve the efficiency of immuno‐electron localization in other model organisms. <inline-graphic xlink:href="ark:/27927/pgj1m9qb38q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />